2020
DOI: 10.1039/d0sm00593b
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun cellulose-based conductive polymer nanofibrous mats: composite scaffolds and their influence on cell behavior with electrical stimulation for nerve tissue engineering

Abstract: Electrospun cellulose-based poly N-vinylpyrrole (PNVPY) and poly (3-hexylthiophene) (P3HT) nanofibrous mats and their influence on nerve cell behavior with electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
0
23
0
2
Order By: Relevance
“…Electrospun fiber diameter, alignment, density, and surface nanotopography have all been shown to affect neuronal and glial behavior [24,[27][28][29]. Additionally, the unique properties of various materials used to generate electrospun fibers, such as biocompatibility, degradation rate, and conductivity ( Figure 1C), can affect cell adhesion, migration, and phenotype [30][31][32]. Fibers can also be further functionalized by incorporating drugs or surface coatings to produce a desirable effect for a given application [1,6,23,33] ( Figure 1D,E).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun fiber diameter, alignment, density, and surface nanotopography have all been shown to affect neuronal and glial behavior [24,[27][28][29]. Additionally, the unique properties of various materials used to generate electrospun fibers, such as biocompatibility, degradation rate, and conductivity ( Figure 1C), can affect cell adhesion, migration, and phenotype [30][31][32]. Fibers can also be further functionalized by incorporating drugs or surface coatings to produce a desirable effect for a given application [1,6,23,33] ( Figure 1D,E).…”
Section: Introductionmentioning
confidence: 99%
“…The biological response studies conducted using Schwann cells revealed improved cell attachment and higher proliferation following five days of incubation [126]. In another study, conductive polymers poly N-vinylpyrrole and poly(3-hexylthiophene) have been used with cellulose for the fabrication of conductive electrospun nanofibrous scaffold and demonstrated positive outcome [127]. In similar trend, many efforts have been devoted using carbon nanotubes [128], poly{[aniline tetramer methacrylamide]-co-[dopamine methacrylamide]-co-[poly(ethylene glycol) methyl ether methacrylate]} [129], and graphene [130].…”
Section: Nerve Tissue Engineeringmentioning
confidence: 99%
“…For nerve regeneration using electrospun textiles, conductive molecules were coelectrospun with polysaccharides or coated on polysaccharidic scaffolds to improve their conductivity for better performances. Zha et al [95] covered electrospun cellulose with poly N-vinylpyrrole and poly(3-hexylthiophene) through an efficient in situ polymerization, and they found increased thickness, porosity, conductivity, and hydrophilicity of the covered scaffolds. In vitro, undifferentiated PC12 cells showed favorable activity and adhesion to the scaffolds.…”
Section: Tissue Engineeringmentioning
confidence: 99%